2017
DOI: 10.17826/cutf.280149
|View full text |Cite
|
Sign up to set email alerts
|

Mianserin’in sıçanlarda streptozotosin ile indüklenen hiperglisemi ve metabolik değişiklikler üzerine etkisi

Abstract: AbstractÖz Purpose: The aim of this study was to investigate possible effects of atypical antidepressant mianserin on glycemia levels and metabolic parameters of normoglycemic and diabetic rats. Material and Methods: Effects of mianserin administration on blood glucose levels in rats were assessed by measuring "fasting blood glucose", "glycosylated haemoglobin" levels and conducting the "oral glucose tolerance test". Changes in metabolic parameters such as food and water consumption and urine and faeces excret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…Our findings regarding long-term mirtazapine use indicate mirtazapine's potential to enhance glucose homeostasis and thus reduce glucose intolerance and IR risk, potentially followed by alleviation of hyperglycemia. Along with previous findings [57,58,60], these results indicate that mirtazapine treatment, particularly long-term treatment, can have beneficial effects on glucose homeostasis, such as reducing glucose levels and improving IS, in animals with DM. However, other clinical studies have reported that mirtazapine-treated animals experienced weight gain [42,61].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings regarding long-term mirtazapine use indicate mirtazapine's potential to enhance glucose homeostasis and thus reduce glucose intolerance and IR risk, potentially followed by alleviation of hyperglycemia. Along with previous findings [57,58,60], these results indicate that mirtazapine treatment, particularly long-term treatment, can have beneficial effects on glucose homeostasis, such as reducing glucose levels and improving IS, in animals with DM. However, other clinical studies have reported that mirtazapine-treated animals experienced weight gain [42,61].…”
Section: Discussionsupporting
confidence: 88%
“…This may be caused by reductions in hyperglycemia, as demonstrated by the alleviation of glucose intolerance in an IPGTT. Studies have found that treatment with mirtazapine and mianserin (a mirtazapine analog) in rats with type 1 DM can reduce blood glucose levels [57,58]. These findings suggest that mirtazapine affects IS by attenuating long-term HFD consumption-induced hypoglycemia because increased insulin signaling reverses the exacerbated metabolic state to ensure glucose homeostasis maintenance.…”
Section: Discussionmentioning
confidence: 99%